CHARACTERISTICS OF SHALLOTS (Allium ascalonicum L) INFLUENCED BY SULFUR APPLICATION IN FLOATING CULTIVATION. - Novikar Saputra Idly; Susilawati; Suwandi, Suwandi (BIOVALENTIA: Biological Research Journal, 2023)
Floating agricultural cultivation presents a viable solution for cultivating in water-rich regions. Among the crops suitable for this system is shallot (Allium ascalonicum L.). This study aimed to assess the effectiveness of sulfur application on shallot plant characteristics (Allium ascalonicum L.) in floating cultivation. Conducted in May 2023 at the Faculty of Agriculture's research pond, Sriwijaya University, the research employed a completely randomized design with sulfur applications (S1: 0 kg ha-1, S2: 30 kg ha-1, S3: 60 kg ha-1, S4: 120 kg ha-1, S5: 240 kg ha-1). Results revealed that tuber diameter exhibited strong determination values (R2: 75%), leaf length, number of leaves, and number of tillers exhibited moderate determination values (R2: 51%, 57% and 56%, respectively), while the relative growth rate showed a weak determination value (R2: 40%). The 60 kg ha-1 sulfur treatment demonstrated the highest chlorophyll content.